Gabon Indigents Scheme : A Social Health Insurance Program for the Poor - Mibindzou Mouelet, Ange; El Idrissi, Moulay Driss Zine Eddine; Robyn, Paul Jacob (World Bank, Washington, DC, 2018)
This paper briefly describes primary health care and accessibility to health care provision in Gabon, and the social health insurance architecture of the GIS. The paper is not intended to provide an analytical and detailed study on health insurance in Gabon. It simply aims to provide a description the GIS in terms of eligibility criteria, targeting, and registration of beneficiaries; special topics related to the management of public funds of the social insurance of the GIS; management of the services offered; and financial sustainability of the GIS. It contributes to the Universal Health Coverage Studies Series on sharing experiences in the field of universal health coverage.